Survival, perpetuation and life cycle of Claviceps oryzae-sativae, causal agent of false smut of rice in Karnataka - K.H. ANAHOSUR2, YASHODA HEGDE1 and (Indian Phytopathology, 2002)
Chlamydospores of Claviceps oryzae-sativae, collected from an infected rice inflorescence, remained viable for upto four months when stored at room temperature (25-35â„ƒ) and in paddy straw at 25-44?while those stored in the refrigerator (4-6? retained their viability for upto seven months. Pseudosclerotia retained their viability upto seven months at room temperature (25-35? and in paddy straw at 25-40?and for nine months in the refrigerator (4-6â„ƒ). The presence of true sclerotia and their germination through stromatic head bearing ascospores were observed for the first time in Karnataka, India.